HOW EXTRACURRICULAR ACTIVITIES CAN STRENGTHEN THE PROFILE OF PANCASILA’S STUDENT? - Nadhifah, Naura; Maf’udah, Syafiyatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Pancasila, Indonesia's basic philosophy, emphasizes the importance of unity, democracy, social justice, and cultural diversity. In this research, researchers want to explore the important role of extracurricular activities in strengthening the profile of Pancasila students. Extracurricular activities provide students with opportunities outside the classroom to develop skills, values, and experiences that align with the core principles of Pancasila. Extracurricular activities also function as a vehicle for social justice. Community service and volunteer work can instill a sense of responsibility and compassion in students, in line with the Pancasila vision of social justice and fair opportunities for all. This research uses a qualitative method with a case study type to reveal and detail extracurricular practices that can strengthen the profile of Pancasila students. This is confirmed by the ongoing case at MI Al-Ihsan Banjarwungu. And in short, the results of this research are able to answer the research title regarding whether extracurricular activities can strengthen the profile of Pancasila students, which has been widely implemented in all educational institutions in Indonesia. The results of this research conclude that extracurricular activities are a vital means of strengthening the profile of Pancasila students. This is what has been implemented at MI Al-Ihsan Banjarwungu. By encouraging unity, democracy, social justice, and cultural diversity, this activity allows students to embody the principles of Pancasila, thereby contributing to a more harmonious, inclusive, and just Indonesian society. This research also contributes to the fact that the Pancasila student profile, which has only been applied through cognitive character education, can also be applied in non-cognitive educational activities.